Efficacy and safety of CD19-specific CAR-T cell-based therapy in secondary central nervous system lymphoma - Zhang, Huanxin; Yan, Zhiling; Wang, Ying; Qi, Yuekun; Hu, Yongxian; Li, Ping; Cao, Jiang; Zhang, Meng; Xiao, Xia; Shi, Ming; Xia, Jieyun; Ma, Sha; et al. (Frontiers in Immunology, 2022)
Encouraging response has been achieved in relapsed/refractory (R/R) B-cell lymphoma treated by chimeric antigen receptor T (CAR-T) cells. The efficacy and safety of CAR-T cells in central nervous system lymphoma (CNSL) are still elusive. Here, we retrospectively analyzed 15 patients with R/R secondary CNSL receiving CD19-specific CAR-T cell-based therapy. The patients were infused with CD19, CD19/CD20 or CD19/CD22 CAR-T cells following a conditioning regimen of cyclophosphamide and fludarabine. The overall response rate was 73.3% (11/15), including 9 (60%) with complete remission (CR) and 2 (13.3%) with partial remission (PR). During a median follow-up of 12 months, the median progression-free survival (PFS) was 4 months, and the median overall survival (OS) was 9 months. Of 12 patients with systemic tumor infiltration, 7 (58.3%) achieved CR in CNS, and 5 (41.7%) achieved CR both systemically and in CNS. Median DOR for CNS and systemic disease were 8 and 4 months, respectively. At the end point of observation, of the 7 patients achieved CNS disease CR, one was still alive with sustained CR of CNS disease and systemic disease. The other 6 died of systemic progression. Of the 15 patients, 11 (73.3%) experienced grades 1-2 CRS, and no patient had grades 3-4 CRS. Immune effector cell-associated neurotoxicity syndrome (ICANS) occurred in 3 (20%) patients, including 1 (6.6%) with grade 4 ICANS. All the CRS or ICANS were manageable. The CD19-specific CAR-T cell-based therapy appeared to be a promising therapeutic approach in secondary CNSL, based on its antitumor effects and an acceptable side effect profile，meanwhile more strategies are needed to maintain the response.